Nitrate perturbation drives carbon cycling in a tropical mangrove estuary - Claris N. Sunjo; Eliot A. Atekwana; Henry M.D. Agbogun; Isaac K. Njilah; Hendratta N. Ali (Journal of Hydrology: Regional Studies, 2025)
Study region: Douala, Cameroon, West Africa Study focus: Tropical mangrove estuaries in sub-Saharan Africa receive far greater amounts of organic and inorganic carbon and pollutants compared to subtropical and temperate estuaries, yet they have not been investigated for their role in local, regional, or global cycling. The lack of data limits our understanding of the contributions of tropical mangrove estuaries in sub-Saharan Africa to global biogeochemical cycling. We document how anthropogenic pollution by nitrate drives carbon cycling in the open water of the tropical mangrove Wouri Estuary. New hydrologic insights: We observed anomalously higher nitrate concentrations of 136–345 µmol/kg over a 15 km range from the estuary mouth. Whole estuary salinity-δ18O mixing is modeled as a two-endmember seawater-freshwater mixing. Although alkalinity and DIC were modeled as a two-endmember seawater-freshwater mixing, a three-component salinity-DIC-δ13CDIC conservative model revealed a mismatch in stations in the lower estuary because of isotopically lower-than-expected δ13CDIC. The isotopically lower than predicted δ13CDIC is from nitrate-driven eutrophication and subsequent production of isotopically light CO2 from organic matter oxidation. Modeled pCO2 more than doubled from 20 times atmospheric in the upper estuary to 50 times atmospheric, increasing the DIC exchanged with the atmosphere. We conclude that anthropogenic nitrate pollution from shipping activities drives carbon cycling near the mouth of this tropical mangrove estuary.